A colonização portuguesa em livros didáticos de História do Brasil: influências historiográficas - Camargo, Helder Mateus de (Universidade Federal de São Carlos, 2024)
This work aims to investigate the Portuguese Colonization in didactic books of Brazilian History under the perspective of the History of Education and the History of School Subjects. It was intended to investigate the form and significance attributed to colonization to identify changes and permanence concerning didactic books. Four didactic pieces were chosen for this analysis, each covering one specific period of the twentieth century. The didactic book is here viewed as a complex cultural aid, responsible for the systematization of a set of information, contents and values. By observing the aforementioned complexity of its nature, the research also aims to identify and explain specific concepts in relation to historical conceptions found in the didactic narrative regarding the Portuguese colonization process. The problematization of the didactic narrative will thus be given from the dialogue under historiographical knowledge, particularly in relation to more influential historiographical currents for each of the periods in question.
The portuguese colonization in didactic books of brazilian History: historiographical influences
Keywords: Colonização portuguesa; Livro didático; História das disciplinas escolares; Ensino de história; Historiografia; Portuguese colonization; Didactic book; History of school subjects; Teaching history; Historiography; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO